2004
DOI: 10.1023/b:heur.0000026267.44673.ed
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Improvement Heuristic for the One-Dimensional Bin Packing Problem

Abstract: We propose in this work a hybrid improvement procedure for the bin packing problem. This heuristic has several features: the use of lower bounding strategies; the generation of initial solutions by reference to the dual min-max problem; the use of load redistribution based on dominance, differencing, and unbalancing; and the inclusion of an improvement process utilizing tabu search. Encouraging results have been obtained for a very wide range of benchmark instances, illustrating the robustness of the algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 24 publications
1
93
0
10
Order By: Relevance
“…Compared with the current best bin packing heuristic approach HP_BP (Alvim et al 2004), the simulated annealing hyper-heuristic is slightly worse in terms of solution quality (see table 6). In fact, HP_BP performed excellently and achieved around 1581 optimal solutions out of 1587 problem instances.…”
Section: Computational Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Compared with the current best bin packing heuristic approach HP_BP (Alvim et al 2004), the simulated annealing hyper-heuristic is slightly worse in terms of solution quality (see table 6). In fact, HP_BP performed excellently and achieved around 1581 optimal solutions out of 1587 problem instances.…”
Section: Computational Resultsmentioning
confidence: 96%
“…Tables 5 and 6 respectively present a comparison of our simulated annealing hyper-heuristic with a hybrid variable neighbourhood search algorithm (Perturbation MBS' + VNS) (Fleszar and Hindi 2002) and a recently proposed hybrid procedure (HP_BP) in (Alvim et al 2004) (the computational results of Perturbation MBS' + VNS on the third group of data sets (Sch_Wae1, Sch_Wae2, Wae_Gau1) are not available in the literature). It can be seen that our simulated annealing hyper-heuristic produced similar results to the hybrid VNS in the first group of data sets and slightly better results in the second group of data sets in terms of solution quality.…”
Section: Computational Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of MBS' followed by a variable neighbourhood search proved an effective combination. Alvim et al (2004) also suggested the use of a hybrid heuristic that incorporates many different techniques. Their approach, HI BP, is probably the most complex one, but it also produces the best results of all reviewed techniques (see Table 2).…”
Section: Related Workmentioning
confidence: 99%
“…In most published works, a classical encoding scheme S is used where S(i) is the index of the bin where item i is placed. [8] proposes a hybrid metaheuristic based on tabu search. [9] proposes a hybrid grouping genetic algorithm which uses the heuristic F F D [1] and the dominance criterion from [10].…”
Section: State Of the Artmentioning
confidence: 99%